Gender stereotypes and the lack of female leaders in RMNI - Abdul Rahman (2010)
This paper looks at how gender stereotypes and prevalent patriarchal ideologies have prevented females from taking up leadership positions in a complex Muslim organization run by Muslim industrial workers in Bintan. The research has been conducted under the context of the existing committee of the religious organization called RMNI. Following the perspectives of feminism, I conducted participant observations and in-depth interviews with 16 respondents to uncover the ways in which gender stereotypes have sustained a system of patriarchy. Islamic scriptures have also been used to legitimize the patriarchal ideology among the members of the organization. I also point out to the everyday life experiences of the industrial workers where the continuous construction of gender may possibly exacerbate gender stereotypes.